Avaliação da permeabilidade dentinária do corante eritrosina utilizado para terapia fotodinâmica - Occhi, Ingrid Gomes Perez (2014)
The photodynamic therapy (PDT) is a treatment which uses a non-toxic dye (photosensitizer) and a suitable light source, and with the oxygen presence they combine to produce cytotoxic agents. The PDT has topical effect, so it is important to know the capacity that photosensitizer has to permeate the tissues so that the bacteria can be reached and inactivated. This study aimed to evaluate the penetration depth of erythrosine in dentin by the technique of photoacoustic spectroscopy by comparing: (a) the permeation depth of erythrosine in two different concentrations (0.3 % and 5 %), (b) the permeation depth of erythrosine in dentin with and without caries-like lesions artificially developed by biofilm formation with S. mutans UA159 for 5 days; (c) and the permeation depth of erythrosine in dentin with caries-like lesions artificially developed by different periods of biofilm formation ( 5, 7 and 10 days). After the Standing Committee on Ethics in Research Involving Humans - COPEP - the State University of Maringá - UEM approval (CAAE 14398113.2.0000.0104), we selected only third molars with incomplete root formation. The teeth were sectioned into dentin blocks with approximately 1 mm thick, which were submitted to the in vitro caries induction model with S. mutans UA159 biofilm formation for 5 days, and the other half of the same tooth was held to be evaluated as the sound group. After the erythrosine (0.3 or 5 %) application on the occlusal surface, the evaluation of the dye permeation was performed by photoacoustic spectroscopy.The erythrosine at 5 % could be detected in a greater average depth (710um) than the erythrosine at 0.3 % (151um), and there was no significant difference between caries-like and the control group. With respect to the different time intervals of biofilm formation , the erythrosine at 5 % followed a higher permeation standard for all the evaluated periods, as well as in the control group. We conclude that erythrosine seems to be promising photosensitizer for application in photodynamic therapy caries. It shown to have a high permeation potential, reaching a sufficient depth to reach the microorganisms, thus making possible its inactivation. The results suggest that the concentration and volume of erythrosine may influence its permeation in dentin. However, the decayed dentine showed similar patterns of healthy dentin, suggesting no change in the permeation of the dye into the dentin route.